How does physical activity alleviate nurse job burnout? The important role of recovery experiences - Li, Xingyi; Zhang, Tianci; Zhao, Guobin; Li, Jie; Chen, Changzhou (Frontiers in Public Health, 2025)
BackgroundIn high-intensity work environments, nurses are significantly affected by job burnout. This study aims to explore the relationship between physical activity and nurses’ job burnout, while examining the mediating role of recovery experiences.MethodConvenience sampling method was employed to recruit 912 nurses. Data were collected using the Physical Activity Rating Scale, Recovery Experience Questionnaire, and Job Burnout Inventory. Empirical analyses were conducted, and the bootstrapping method was applied to test the mediating effects of recovery experiences.ResultsPhysical activity significantly and negatively related nurses’ job burnout (β = −0.554, p < 0.01). The mediating effects of psychological detachment [95% CI (−0.217 −0.168)], relaxation experience [95% CI (−0.081 −0.045)], and mastery experience [95% CI (−0.228 −0.177)] in the relationship between physical activity and job burnout were confirmed. However, the mediating effect of control experience [95% CI (−0.020 0.001)] was not statistically significant.ConclusionThis study identifies a significant negative association between physical activity and job burnout among nurses, and highlights the multidimensional contributions of recovery experiences to this association. The findings provide empirical evidence that may inform strategies for enhancing nurses’ occupational health.